Penegakan Hukum Pidana terhadap Pelaku Vandalisme pada Rambu Lalu Lintas: - Kadek Putra Dwi Payana; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2022)
Vandalism has quite a negative impact on human life such as disrupting the function of public facilities, for example, vandalism in the form of graffiti on traffic signs which in addition to damaging the function of traffic signs can also endanger road users. Therefore, it is necessary to enforce the law on the crime of vandalism in order to provide a deterrent effect by giving sanctions to the perpetrators of vandalism. The purpose of this study is to determine the legal arrangements against vandalism perpetrators on traffic signs and to discuss criminal sanctions that can be imposed on perpetrators of vandalism on traffic signs. The research method that the author uses is normative legal research. The sources of legal material in this study consist of secondary, primary and tertiary legal sources used in this study. These materials are collected by means of recording techniques, file systems, and document studies which will be analyzed systematically. in Article 275 paragraph (2) of Law Number 22 of 2009 concerning Road Traffic and Transportation. The author suggests to the government to immediately make a specific law, and the public to immediately report it to the authorities if there are acts of vandalism